Ebola Virus Glycoprotein IgG Seroprevalence in Community Previously Affected by Ebola, Sierra Leone - Manno, Daniela; Ayieko, Philip; Ishola, David; Afolabi, Muhammed O.; Rogers, Baimba; Baiden, Frank; Serry-Bangura, Alimamy; Bah, Osman M.; Köhn, Brian; Swaray, Ibrahim; Owusu-Kyei, Kwabena; Otieno, Godfrey T.; et al. (Emerging infectious diseases, 2022)
We explored the association of Ebola virus antibody seropositivity and concentration with potential risk factors for infection. Among 1,282 adults and children from a community affected by the 2014-2016 Ebola outbreak in Sierra Leone, 8% were seropositive for virus antibodies but never experienced disease symptoms. Antibody concentration increased with age.